Koordinasi dan Usaha Koordinasi dalam Organisasi : Sebuah Kerangka Studi - Nia Juliawati (Jurnal Administrasi Bisnis, 2012)
Coordination or management of dependencies between activities within an organiza-tion, as a result of decomposition and specialization of works, is an important issuethat has been associated with the success or failure of cooperative works. Coordina-tion mechanism through the establishment of rules and procedures that underlie thecooperation is often not sufficient to make the coordination really run as expected.This paper describes the underlying need for attention to the dynamic aspects of theorganization’s working life, which influence the effectiveness of coordination . Thestructural-mechanistic approach need to be complemented with an understanding ofthe actors’ perspectives and organization’s culture.Keywords: Koordinasi, budaya, aktor, pendekatan mekanistik, pendekatan organik